2,2'-[2,5-Bis(hexyloxy)-1,4-phenylene]dithiophene - Teh, Chin Hoong; Mat Salleh, Muhammad; Mohamed Tahir, Mohamed Ibrahim; Daik, Rusli; Kassim, Mohammad (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C26H34O2S2, comprises one half-molecule located on an inversion centre. The thiophene groups are twisted relative to the benzene ring, making a dihedral angle of 5.30 (7)°, and the n-hexyl groups are in a fully extended conformation. In the crystal, there are short C—H(...)π contacts involving the thiophene groups.